PENGARUH KEPUASAN KERJA TERHADAP PRESTASI KERJA MELALUI MOTIVASI : ( Studi Kasus Pada Pizza Hut Cabang Ahmad Yani Padang) - Sonia Maharani; Agussalim M; Novi Yanti (Matua Jurnal, 2021)
This study aims to examine and analyze the Effect of Job Satisfaction on Job Performance through Motivation (Case Study in Pizza Hut Ahmad Yani Branch Padang). "Where variable X is Job Satisfaction and Motivation dependent variable Job Performance (Case Study on Pizza Hut Ahmad Yani Branch Padang ) ". This study uses a classic assumption test consisting of the Normality test, the Herosadisity Test, the multicoreanerity test and the multiple regression test, the determinant test and the path test while the hypothesis is tested using the t test and F test. The results of this study are the variable job satisfaction has a negative and significant effect on the work performance of Pizza Hut Ahmad Yani Branch Padang employees Motivation variable has a positive and significant effect on the work preservation of Pizza Hut Ahmad Yani Branch Padang employees and job satisfaction indirectly has a significant effect on work performance Pizza Hut Branch Ahmad Yani Padang employees through motivation